Influence of a curcumin derivative on hIAPP aggregation in the absence and presence of lipid membranes. Issue 5 (20th November 2015) - Pithadia, Amit S.; Bhunia, Anirban; Sribalan, Rajendran; Padmini, Vediappen; Fierke, Carol A.; Ramamoorthy, Ayyalusamy
Abstract : The deposition of aggregates of human islet amyloid polypeptide (hIAPP) has been correlated with the death of β-cells in type II diabetes mellitus. Abstract : The deposition of aggregates of human islet amyloid polypeptide (hIAPP) has been correlated with the death of β-cells in type II diabetes mellitus. The actual molecular mechanism of cell death remains largely unknown; however, it has been postulated that the process of aggregation from monomeric hIAPP is closely involved. A possible cause of cellular toxicity may be through the disruption of structural integrity of the cell membrane by IAPP. Herein, a water-soluble curcumin derivative, CurDAc, is used to investigate the mitigation of hIAPP aggregation in the absence and presence of lipid membrane.